Jenis Jenis Burung di Kawasan Kampus 4 Universitas Ahmad Dahlan Yogyakarta - Wicaksana, Ragil Yoga Mandhala; Setyawan, Danni; Resdianningsih, Kenni; Al-Isnaeni, Bilqies Amalia; Subagja, Roby Ahmad; Husna; Utami, Inggita (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
Campus 4 of Ahmad Dahlan University (UAD) is a new campus located in Bantul Regency, Yogyakarta. Campus 4 of UAD area is one of an important habitat pocket for bird species in Bantul Regency. Land use change due to development of urban settlement in this area can affect the existing bird species. The objectiveof this research is to collect data on bird species in the Campus 4 of UAD area. The research was conducted in three different months, namely September 2019, January 2020, and September 2020. The method used in this study was the observation of the roaming method combined with the Visual Encounter Survey (VES). Observations were carried out at three different times, from morning to evening. The birds that observed were identified using a field guide book entitled Burung-Burung diSumatera, Jawa, Bali dan Kalimantan. Recorded bird species data then validated and matched using a book entitled Daftar Burung Daerah Istimewa Yogyakarta especially on Bantul regency area.Based on the results of research conducted, the species of birds observed in the Campus 4 of UAD area consist of 21 species from 12 families. The number of species has increased from 7 species in September 2019 to 19 species in September 2020.